The New Zealand Health and Safety System in 2024 - O'Brien, Mike (New Zealand Journal of Health and Safety Practice, 2024)
Welcome to the second edition of the New Zealand Journal of Health and Safety Practice. The first edition explored issues relevant to health and safety practice in 2024. This edition’s theme is the New Zealand workplace health and safety system. It appears as a response to the Coalition Government’s proposed “Reform [of] health and safety law and regulation” (Luxon & Seymour, 2023, p. 5). This has led to a “Major health and safety consultation” (Van Velden, 2024).